2021
DOI: 10.3390/ijerph18136841
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators of Nurses’ and Physicians’ Willingness to Work during a Respiratory Disease Outbreak: A Mixed-Methods Systematic Review

Abstract: This review was undertaken to identify the perceived barriers and facilitators of nurses’ and physicians’ willingness to work during a respiratory disease outbreak. This mixed-methods systematic review involved the extraction of data from the electronic databases PubMed, Web of Science, CINAHL, and PsycINFO and from a manual search of articles published between 2003 and April 2021. The quality of the included studies was assessed using a mixed-method appraisal tool. A total of 29 studies were eligible for incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
(169 reference statements)
0
4
0
Order By: Relevance
“…Many challenges are inherent to the nursing role (Botha et al, 2015), but prolonged or intense challenge from a pandemic generates fear and an atmosphere of unease while caring for infected patients (Vizheh et al, 2020). Relevant and current information, resources and disaster‐based training (Al Thobaity & Alshammari, 2020; Lee et al, 2021), better preparedness and building healthcare professionals' resilience prior to pandemics (Aiello et al, 2011) may off‐set this fear.…”
Section: Discussionmentioning
confidence: 99%
“…Many challenges are inherent to the nursing role (Botha et al, 2015), but prolonged or intense challenge from a pandemic generates fear and an atmosphere of unease while caring for infected patients (Vizheh et al, 2020). Relevant and current information, resources and disaster‐based training (Al Thobaity & Alshammari, 2020; Lee et al, 2021), better preparedness and building healthcare professionals' resilience prior to pandemics (Aiello et al, 2011) may off‐set this fear.…”
Section: Discussionmentioning
confidence: 99%
“…This paper primarily describes the qualitative part of the study. We chose a qualitative approach as it could provide more in-depth knowledge and help us explore meanings and experiences influencing the dynamics of reallocation (6,14).…”
Section: Designmentioning
confidence: 99%
“…Previous research has studied barriers to reallocation and identified features of successful staff reallocation plans (2,3,(5)(6)(7)(8). Especially, staff's ability and willingness to work have been perceived as important determinants of working behavior during a pandemic (2,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation